2019
DOI: 10.3390/agronomy9090547
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Herbicide Use: Study on Spreading and Evaporation Characteristics of Glyphosate-Organic Silicone Mixture Droplets on Weed Leaves

Abstract: Herbicide deposition rate can be affected by the leaf surface features of weeds and have a significant impact on the overall efficacy. In this paper, an orthogonal experiment was conducted to investigate the differences of droplet evaporation and spreading characteristics corresponding to weed leaf surface with hairy, waxy and rough (ridged) structures. Three weed species—Descurainia sophia, Lepidium lotifolium, and Lolium temulentum—were included in the study, representing these three leaf structures respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The need for the addition of adjuvants to glyphosate solutions was previously reported by Castro et al [1], who claimed that glyphosate alone or in its different salt forms could not effectively penetrate specific structural elements of plant surfaces. This was also supported by Li et al [6], who reported that an added surfactant leads to improved droplet coverage on leaves and therefore to better absorption of glyphosate.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The need for the addition of adjuvants to glyphosate solutions was previously reported by Castro et al [1], who claimed that glyphosate alone or in its different salt forms could not effectively penetrate specific structural elements of plant surfaces. This was also supported by Li et al [6], who reported that an added surfactant leads to improved droplet coverage on leaves and therefore to better absorption of glyphosate.…”
Section: Discussionsupporting
confidence: 62%
“…The absorption process requires thorough research around the various parameters that affect retention, spreading, penetration, and finally the translocation of pesticide substances within the plant tissues. Therefore, some of the important parameters that should be taken into account are the specific characteristics of the plant surface (i.e., wax composition and leaf roughness) and the traits of the sprayed liquid [6]. Regarding the leaf surface characteristics that affect spray adhesion, the trichomes, the cuticular membrane and the extent of wax act as interceptors to droplet spreading [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the use of an organosilicone surfactant can contribute to a significant increase in the coverage of barnyardgrass leaves by liquid drops [33]. However, it should be remembered that an increase in leaf wetting may lead to an increase in the evaporation rate of spray liquid drops [34]. Adjuvants are substances that do not have a direct herbicidal effect, but they can modify the properties of the spraying liquid, which can lead to an increase in the effectiveness of herbicides [35].…”
Section: Discussionmentioning
confidence: 99%
“…Herbicide efficacy can be significantly enhanced by the addition of adjuvants, leading to increased uptake and translocation of the active ingredient [9]. In relation to targeting efficiency, the addition of adjuvants either in the formulated products or in the tank mixtures has been reported to improve glyphosate absorption and translocation in the plant tissues [1,10].…”
Section: Introductionmentioning
confidence: 99%